Population Pharmacokinetics of Vancomycin in Pregnant Women - Goyal, Rahul K.; Moffett, Brady S.; Gobburu, Jogarao V. S.; Al Mohajer, Mayar (Frontiers in Pharmacology, 2022)
Objective: Vancomycin is a glycopeptide antibacterial indicated for serious gram-positive infections. Pharmacokinetics (PK) of vancomycin have not been described in pregnant women. This study aims to characterize the PK disposition of vancomycin in pregnant women based on data acquired from a database of routine hospital care for therapeutic drug monitoring to better inform dosing decisions. Methods: In this study, plasma drug concentration data from 34 pregnant hospitalized women who were administered intravenous vancomycin was analyzed. A population pharmacokinetic (PPK) model was developed using non-linear mixed effects modeling. Model selection was based on statistical criterion, graphical analysis, and physiologic relevance. Using the final model AUC0-24 (PK efficacy index of vancomycin) was compared with non-pregnant population. Results: Vancomycin PK in pregnant women were best described by a two-compartment model with first-order elimination and the following parameters: clearance (inter individual variability) of 7.64 L/hr (32%), central volume of 67.35 L, inter-compartmental clearance of 9.06 L/hr, and peripheral volume of 37.5 L in a typical patient with 175 mL/min creatinine clearance (CRCL) and 45 kg fat-free mass (FFM). The calculated geometric mean of AUC0-24 for the pregnant population was 223 ug.h/ mL and 226 ug.h/ mL for the non-pregnant population. Conclusion: Our analysis suggests that vancomycin PK in pregnant women is consistent with non-pregnant adults and the dosing regimens used for non-pregnant patients may also be applicable to pregnant patients.